Visible-Light Excited Luminescent Thermometer Based on Single Lanthanide Organic Frameworks - Li, Liang
Isostructural lanthanide organic frameworks (Me2NH2)(3)[Ln(3)(FDC)(4)(NO3)(4)]center dot 4H(2)O (Ln = Eu (1), Gd (2), Tb (3), H2FDC = 9-fluorenone-2,7-dicarboxylic acid), synthesized under solvothermal conditions, feature a Ln-O-C rod-packing 3D framework. Time-resolved luminescence studies show that in 1 the energy difference between the H2FDC triplet excited state (17794 cm(-1)) and the D-5(0) Eu3+ level (17241 cm(-1)) is small enough to allow a strong thermally activated ion-to-ligand back energy transfer. Whereas the emission of the ligand is essentially constant the D-5(0)-> F-7(2) intensity is quenched when the temperature increases from 12 to 320 K, rendering 1 the first single-lanthanide organic framework ratiometric luminescent thermometer based on ion-to-ligand back energy transfer. More importantly, this material is also the first example of a metal organic framework thermometer operative over a wide temperature range including the physiological (12-320 K), upon excitation with visible light (450 nm).